Conflict Management Model Based on Behaviorism and Effective Communication in Social Security Treatment Management in Markazi Province - Mirzaei, Gholamreza; Ghasemi, Morteza; Majidi, Maryam; Mehtari Arani, Mohammad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: Human resource management is one of the most complex and challenging topics in contemporary organizations. One of the challenging aspects of this field is conflict management among organizational employees. The main goal of this study is to present a conflict management model based on behaviorism and effective communication in the Social Security Treatment Management of Markazi Province.Methodology: The statistical population of this qualitative research consists of experts and managers from the Social Security Treatment Management of Markazi Province. Snowball sampling is used in this study. The sample size is set at 16 individuals. To collect qualitative data, interviews were conducted with experts. The data were analyzed using directed content analysis.Findings: Ultimately, 58 subcategories were identified within 17 main categories, which were introduced as dimensions of conflict management in two sections: behaviorism and effective communication.Conclusion: Therefore, based on these dimensions, successful implementation of conflict management models can be achieved in organizations.